Early Word Segmentation Behind the Mask - Frota, Sónia; Pejovic, Jovana; Cruz, Marisa; Severino, Cátia; Vigário, Marina (Frontiers in Psychology, 2022)
Infants have been shown to rely both on auditory and visual cues when processing speech. We investigated the impact of COVID-related changes, in particular of face masks, in early word segmentation. Following up on work by Butler and Frota (2018), who showed that by 4 months infants already segmented targets presented auditorily at utterance-edge position, and using the same visual familiarization paradigm, 7-9-month-old infants performed an auditory and an audiovisual word segmentation experiment in two conditions: without and with a N95 face mask. Analysis of acoustic and visual cues showed changes in face-masked speech affecting the amount, weight, and location of cues, with edge position less salient than medial position in face-masked speech. Results revealed no evidence for segmentation, not even at edge position, regardless of mask condition and auditory or visual speech presentation. However, in the audiovisual experiment infants attended more to the screen during test trials when familiarized with without mask speech. Also, infants attended more to the mouth and less to the eyes in without mask than with mask. In addition, evidence for an advantage of the utterance-edge position in emerging segmentation abilities was found. Thus, audiovisual information provided some support to developing word segmentation. We compared 7-9-monthers segmentation ability observed in the Butler and Frota pre-COVID study with the current auditory without mask data. Mean looking time for edge was significantly higher than unfamiliar in the previous study only. Measures of cognitive and language development obtained with the CSBS scales showed that the infants of the current study scored significantly lower than same age infants from the CSBS (pre-COVID) normative data. Our results suggest an overall effect of the pandemics on early segmentation abilities and language development, calling for longitudinal studies to determine how development proceeds.